The role of cascade reporting integrated with breakpoint to minimum inhibitory concentration quotient (minimum inhibitory concentration therapeutic index) and minimum inhibitory concentration guiding table on clinical microbiology reporting of culture-proven bloodstream infections - Sarumathi Dhandapani; Ketan Priyadarshi; Deepashree Rajshekar; Monika Sivaradjy; Haritha Madigubba; Apurba Sankar Sastry (Journal of Current Research in Scientific Medicine)
Background: The breakpoint to minimum inhibitory concentration (MIC) quotient (BMQ) of an antimicrobial agent is the ratio of susceptible breakpoint divided by MIC of the test isolate. The higher the BMQ, the better is the therapeutic efficacy. The reporting of BMQ and MIC guiding table (MGT) when integrated with cascade reporting is more useful, especially in bloodstream infections. Methodology: The study period was of 2 years (June 2019–May 2021). The blood culture (BC) isolates were subjected to susceptibility testing by VITEK® 2 automated antimicrobial susceptibility test (AST) system for all the antimicrobials at a time but reported only selectively (cascade reporting). The BMQ of the susceptible antibiotics was calculated and the MGT was developed by using a specialized “clinical microbiology reporting software.” Both the BMQ and MGT were included in the clinical microbiology report along with the suggested “drug of choice” (DOC) based on the highest BMQ. Results: A total of 2644 out of 56,663 BC episodes were included. Of all the AST results, 57.0% (1, 508) were found to be susceptible to ≥1 first-line antimicrobials tested and 8.7% (230) were found to be resistant to all antimicrobials tested. Overall in about 16.7% of episodes, BMQ-DOC reported was found to be different compared to the raw MIC-DOC, and the difference was found to be maximum for Pseudomonas aeruginosa (50.3%). Conclusion: Reporting of BMQ and MGT is impactful only when it is integrated with cascade reporting as BMQ can only be taken into consideration while comparing the agents of similar spectrum.